The Manifestation of EFL Teachers’ Self-Efficacy and TPACK with their Teaching Performance - Ainur Rosyidah Azmie Putry; Puji Astuti; Zulfa Sakhiyya (Universitas Negeri Semarang, 2022)
Teachers play very important roles on students learning, especially during the pandemic situation where emergency online learning has replaced the traditional classroom learning. Some factors can influence teachers’ performance such as teachers’ self-efficacy and TPACK (technological pedagogical content knowledge) framework. Here, the teacher participants have perception of their capabilities to accomplish the task by integrating content, pedagogy, and technology. This paper addresses the issue by employing a qualitative case study to investigate the manifestation of teacher participants’ self-efficacy and TPACK, as well as the relation between the two with teaching performance. Three EFL teachers at SMA 2 Demak are purposefully selected as the subjects of the research. The findings reveal that (1) the dominant source of self-efficacy in teacher A is psychological and emotional arousal but in teacher B and teacher C is mastery experience. (2) based on the statistical measurement, the score of teacher A’s self-efficacy was 65.0% and 63.9% in the TPACK framework. The score of self-efficacy in teacher B was 85.0% and 68.5% in TPACK framework. In teacher C, the score of both terms was 83.3%. (3) some factors of teacher participants’ self-efficacy affected the successful level of teaching performance. In a nutshell, self-efficacy fosters teachers’ motivation, develops teachers’ TPACK, and influences the successful level of teaching performance to implement TPACK framework. The present research provided a valuable knowledge about the importance of self-efficacy and TPACK framework and suggestion to construct some developmental programs to encourage student teachers in preparing better teaching learning process in the future.